ASSESSMENT OF THE LEVEL OF ECONOMIC SAFETY OF MINING ENTERPRISES - yazykovskiy, bohdan (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
The article substantiates the importance of objective assessment of economic security of enterprises, which serves as a basis for appropriate operational response, management decisions to reduce / level the impact of destructive factors on economic security, development and implementation of a system of measures to strengthen it. Approaches to assessing the level of economic security are systematized. The characteristic features, advantages and disadvantages of scientific and methodological approaches to determining economic security are described. Methods of diagnosing economic security and methods that can be used to calculate the integrated indicator of economic security of mining enterprises are described. The main groups of indicators of the internal environment that need to be assessed to determine the level of economic security of mining enterprises in terms of components are described. The main problems that cause risks and threats that negatively affect the economic security of mining enterprises have been identified. The groups of environmental factors that affect the economic security of mining enterprises are identified, the need for their study, evaluation, clarification of their impact on the economic security of enterprises is substantiated. The focus is on the main aspects that determine the outcome of economic security assessment and which should be followed to ensure the complexity and systemic nature of these procedures in the system of assessing the level of economic security of mining enterprises.